Meniere's disease: Structural considerations in early cochlea hydrops - Daniel J. Pender (Laryngoscope Investigative Otolaryngology)
Abstract Objective Structural features of the human cochlea may control early lesion formation in endolymphatic hydrops. This process may hinge on three structural features: the flattened spiral shape of the human cochlea, the toroidal configuration of the distended cochlea duct, and the distensibility characteristics of Reissner's membrane. An analytical method is presented to assess the variation in hydropic distention that may occur in the several turns of the cochlea due to these structural features. Methods A normal human cochlea is used to illustrate the method of analysis. Structural dimensions were taken from a mid‐modiolar section. Reissner's membrane was projected to assume a spiral toroid shape as it distends. Peak membrane stress proclivities in each cochlea turn were calculated analytically. Membrane strain was assessed from a collagen model of Reissner's membrane. Sagittal membrane displacements were quantified geometrically. Results Stress levels in Reissner's membrane were projected to be the lowest in the lower basal turn and to increase progressively to a peak value in the apex. Strain in Reissner's membrane in the apical turn was projected to be substantially higher than in the lower turns. Sagittal displacement of Reissner's membrane was projected to be most pronounced in the apical turn in all the stages of early cochlea hydrops. Conclusion Structural features appear to underlie a differential susceptibility to hydrops in the human cochlea. The flattened spiral shape of the human cochlea coupled with the anticlastic configuration and the distensile characteristics of Reissner's membrane are projected to result in distinct histological stages as hydropic disease in the cochlea progresses.